Adaptive interaction design model for location-based augmented reality in cultural heritage sites - Eidlan Hadi Mazlan, Hanafi (2024)
Augmented Reality (AR) has enabled travel and tourism industries to advance beyond the conventional sources of information providers. Adaptive Location-Based Augmented Reality (LBAR) may assist in providing dynamic media and interactivity, which needs a new set of interaction techniques to enhance and enrich the application usage by visitors in cultural heritage sites. However, research in adaptive interaction design models remains scarce, especially on adaptive interaction in LBAR in cultural heritage sites. Therefore, the objectives of this study are to identify the modalities of interaction techniques which are essentials for LBAR; to identify users needs and preferred interaction techniques when using LBAR in cultural heritage sites; to develop an adaptive interaction design model based on identified user needs and preferred interaction techniques on LBAR; and to validate the interaction model using user validation. This study employed the design science research method, which includes focus group discussion, expert review, user requirements, and usability testing. Use cases and user persona were developed during focus group discussion, which led to the identification of user needs and preferred interaction techniques. This and previous studies have yielded modalities which are unimodal, multimodal, and adaptive and were then included in the adaptive interaction design model. Next, four experts reviewed and concluded that the adaptive interaction design model is usable for the development of location-based mobile AR applications for cultural heritage sites. Then, a prototype named MelakAR was developed as a proof-of-concept and tested by 35 participants in terms of its usability. Based on the usability testing, participants agreed on its ease of use; its perceived usefulness, and its satisfaction. The results show that the participants were indeed satisfied with using the MelakAR app in Melaka cultural heritage sites. The main outcome of this study is an adaptive interaction design model that provides guidelines for future developers to incorporate adaptive interaction strategies for LBAR in cultural heritage sites.